The Role of Standardized Tests and Non-Standardized Tests in Learning Assessment and Evaluation - Sari, Desi Puspita; Arbeni, Wawan; Putri, Devi Yolanda; Wardayanti, Elsa; Syahroni, Dimas (Lembaga Riset Mutiara Akbar, 2026)
Learning evaluation is an integral part of the educational process, serving to systematically and continuously assess student competency achievement. One of the main instruments in learning evaluation is testing, both standardized and non-standardized tests, each of which has different characteristics, functions, and objectives. This study aims to examine the role of standardized and non-standardized tests in the assessment and evaluation of learning and their relevance in educational practice. The research method used is a literature study by analyzing various literature sources such as books, scientific journals, and policy documents related to learning evaluation. The results of the study indicate that standardized tests have a high level of validity and reliability, making them suitable for measuring learning outcomes broadly and objectively, while non-standardized tests are more flexible and contextual because they are tailored to classroom learning needs. Both types of tests complement each other in providing a complete picture of student learning outcomes and processes. Therefore, educators need to understand and utilize standardized and non-standardized tests proportionally so that learning assessment and evaluation can be carried out effectively, fairly, and meaningfully.